TEXT IN CONTEMPORARY ART - Hart, Natalija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
In the following pages we will take a brief look at how the use of text has developed and how it has found itself being used in today’s comtemporary art. The author will be drawing from the author’s experience gained in an exhibition at the Liverpool Tate (UK) that the author has recently been to with the Sedici group, a private art group that the author belongs to. Here the author looks at some of these works seen at the exhibition dedicated to the use of text in art ,and shares her thoughts on the subject.